New records of gelatinous zooplankton from an oceanic island in the Eastern Tropical Pacific - Corrales Ugalde, Marco (2017)
Gelatinous zooplankton are an abundant and diverse group of animals in the pelagic environment. However, knowledge of species diversity and spatial distributions, as well as their ecological role, is scarce. We present information of epi- and mesopelagic gelatinous zooplankton recorded by the ‘DeepSee’ submersible between 2006 and 2012 at Isla del Coco (Cocos Island), Costa Rica, an oceanic island in the Eastern Tropical Pacific. Two species of scyphomedusae, three species of hydromedusae, two genera of siphonophores, and two species of ctenophores were observed in the videos, at depths between 50 and 400 m. None of these species had been previously recorded in the waters around the island. Furthermore, except for the jellyfish Pelagia noctiluca and a siphonophore in the genus Praya, all are new records for Costa Rican waters. This study also includes the first record of the cnidarians Modeeria rotunda, Solmissus sp., Halitrephes maasi and Apolemia spp., and the ctenophore Thalassocalyce inconstans in the Eastern Tropical Pacific. We show that surveys in regions with little information about gelatinous zooplankton may broaden our knowledge of their natural history and may result in new records of gelatinous species.